2008
DOI: 10.1002/hep.22404
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1 secreted by adipose tissue induces direct lipid accumulation in hepatocytes

Abstract: For many years, adipose tissue has been mainly considered as an inert reservoir for storing triglycerides. Since the discovery that adipocytes may secrete a variety of bioactive molecules (hormones, chemokines, and cytokines), an endocrine and paracrine role for white adipose tissue (WAT) in the regulation of energy balance and other physiological processes has been established, particularly with regard to brain and muscle. In contrast, little is known about the interactions of WAT with liver. Hence, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 47 publications
6
57
0
Order By: Relevance
“…was demonstrated that MCP-1 is capable of inducing triglyceride accumulation in hepatocytes in vitro in a time-and dose-dependent manner (6). Indeed, we found that diet-induced steatosis was significantly reduced in MLK3-deficient mice (Fig.…”
Section: E553 Role Of Mlk3 In Diet-induced Metabolic Dysfunctionsupporting
confidence: 53%
See 1 more Smart Citation
“…was demonstrated that MCP-1 is capable of inducing triglyceride accumulation in hepatocytes in vitro in a time-and dose-dependent manner (6). Indeed, we found that diet-induced steatosis was significantly reduced in MLK3-deficient mice (Fig.…”
Section: E553 Role Of Mlk3 In Diet-induced Metabolic Dysfunctionsupporting
confidence: 53%
“…Thus, it has been demonstrated that loss of MCP-1 reduced diet-induced hepatic steatosis, whereas overexpression of MCP1 or incubation of hepatocytes with MCP-1 increased triglyceride accumulation (22). In addition, it was demonstrated that MCP-1, but not IL-6 or IL-8, is capable of inducing triglyceride accumulation in hepatocytes in vitro in a time-and dose-dependent manner (6). Consistent with decreased MCP-1 expression, we observed decreased diet-induced steatosis in MLK3-KO mice (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…MCP-1 causes cholesterol accumulation in hepatocytes ( 28 ), and HDL receptors in hepatocytes contribute to cholesterol metabolism through the RCT process, including the generation of HDL and cholesterol ester uptake from HDL-cholesterol. Thus, we evaluated the effects of MCP-1 on the activities of HDL receptors in hepatocytes and the this effect was the result of a reduction in the expression of the total protein or in the cell-surface expression of the HDL transporters was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…address the direct effects of adipocyte factors generated in response to PFKFB3/iPFK2 overexpression on hepatocyte metabolic and inflammatory responses, adipocyte-conditioned medium was used to treat WT mouse primary hepatocytes as described previously (11,33,34). Palmitate was supplemented into hepatocyte medium to induce fat deposition and inflammatory responses.…”
Section: Adipocyte-derived Factors Dissociate Hepatocyte Inflammatorymentioning
confidence: 99%